Forecasting The Number Of Customers Using The Box-Jenkins (Arima) And Linear Regressionmethod (Case Study: PT. AIA Financial LPG Sunrise Agency) - Amalyanda Azhari; Sri Lestari (Proceeding International Conference on Information Technology and Business, 2019)
Forecasting is one of the important inputs for a company in the investment decision-making process. We realize that in the forecasting process there are often inaccuracies in the results of forecasting, but forecasting must be done because all organizations operate in an environment that contains an element of uncertainty. In addition, decision-making must still be taken which will affect the future of the company. The method used in this research is Linear Regression and Arima. Based on these studies it was found that this method is suitable for predicting the number of customers with a case study of the number of customers at PT. AIA Financial LPG Sunrise Agency. This study provides the results of forecasting the number of customers at PT. AIA Financial LPG Sunrise Agency and produce data that can be used as a reference for what needs to be done in the future so that the policies taken by the company can be better for the company in the future.Keywords: Forecasting, PT.AIA Financial LPG Sunrise Agency, Linear Regression, Arima